Epidemiology of endometriosis in women of Arab ancestry - Mousa, M (2021)
Introduction Investigating the epidemiology of endometriosis in women of Arab ancestry, in the context of regionally important environmental and genetic effects, will provide us with a better understanding on the endometriosis phenome across different populations. Under the following initiative, the Middle Eastern Women Research Association: the MAR’A project, the study aimed to investigate for the first time in women of Arab ancestry: (1) Associations of symptomatology, risk factors, phenotypic profile, and comorbidities with endometriosis (2) Assess the impact of endometriosis on health-related quality of life (HRQoL), work productivity, activity impairment, physical activity, and diagnostic delay (3) Conduct a candidate gene association study (CGAS) on variants in wingless-type MMTV integration site family member 4 (WNT4) and the Vezatin (VEZT) in women with endometriosis.